2016
DOI: 10.3168/jds.2015-10060
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian integration of sensor information and a multivariate dynamic linear model for prediction of dairy cow mastitis

Abstract: Rapid detection of dairy cow mastitis is important so corrective action can be taken as soon as possible. Automatically collected sensor data used to monitor the performance and the health state of the cow could be useful for rapid detection of mastitis while reducing the labor needs for monitoring. The state of the art in combining sensor data to predict clinical mastitis still does not perform well enough to be applied in practice. Our objective was to combine a multivariate dynamic linear model (DLM) with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 38 publications
0
51
0
2
Order By: Relevance
“…Early diagnosis is very important due to the high costs of mastitis. However, most current detection systems do not meet the high accuracy required for clinical diagnosis needs of mastitis (Jensen et al, 2016). Nowadays, somatic cell count (SCC) and California mastitis test (CMT) are often used in the diagnosis of mastitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early diagnosis is very important due to the high costs of mastitis. However, most current detection systems do not meet the high accuracy required for clinical diagnosis needs of mastitis (Jensen et al, 2016). Nowadays, somatic cell count (SCC) and California mastitis test (CMT) are often used in the diagnosis of mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the fact that the performances of the most current bovine mastitis detection systems do not meet the high accuracy required for clinical diagnosis needs of mastitis (Jensen et al, 2016), the main purpose of this study is to identify potential genes that can be used as biomarkers for the diagnosis of E. coli mastitis. Although these genes have been identified in this study and had been preliminarily confirmed in previous animal or cell Cytokine-cytokine receptor interaction 8.26E−09 CCL3, IL6, CCL2, CCL20, IL18, IL1B, CXCL8, IL1A bta04621 NOD-like receptor signaling pathway 6.70E−08 IL6, CCL2, IL18, IL1B, NFKBIA, CXCL8 bta04620…”
Section: Degsmentioning
confidence: 99%
See 1 more Smart Citation
“…The naive Bayes method relies on independence between the input variables, but it performs surprisingly well even under conditions that might be considered suboptimal for the algorithm (Domingos and Pazzani, 1997;Friedman, 1997). Despite the relative simplicity of its algorithm, naive Bayes is still widely used (Jensen et al, 2016;Drury et al, 2017). Random forest (Breiman, 2001) is another machine-learning method that is successfully implemented in a wide variety of fields, including animal science (Shahinfar et al, 2014;Machado et al, 2015;Brieuc et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic linear model have been used in monitoring bulk tank SCC in milk (Thysen, 1993), in detecting estrus and diseases in dairy cattle (de Mol et al, 1999), and in monitoring daily milk production (Van Bebber et al, 1999). In recent years, DLM have been used to estimate the production potential of cows as a basis for optimal replacement policies (Nielsen et al, 2010), for prediction of dairy cow mastitis (Jensen et al, 2016), as well as to determine whether dairy cows with subclinical mammary infections recover after antibiotic treatment (Jørgensen et al, 2016). The model constructed by Van Bebber et al (1999) was used to detect significant changes in the milk production of both individual cows and an entire herd, and could be used in exploiting changes occurring during normal (non-EVOP) production flow in the dairy herd.…”
Section: Introductionmentioning
confidence: 99%